Fundamentación de la praxis pedagógica en el programa de Arquitectura de la Universidad de San Buenaventura (2007)
The Faculty of Architecture at Saint Bonaventure University, Medellin branch, has been developing for a few years, a pedagogical process where different pedagogical, epistemological and psychological types of approaches are integrated; the authors have wanted to synthesize this pedagogical proposal, as someone who keeps a diary or journal: first it is experienced and then it is reported. In this foundation of the pedagogical praxis, it is aimed at collecting the experiences the students have gone through, backing up and articulating them with other current educational experiences and approaches, taking as an important framework the Bonaventurian Educational Project and the macro- pedagogical proposal, the Franciscan paideia, these being the principles which guide the University educational action. The pedagogical proposal, which is presented here, is open to the university community, since the curriculum is conceived as open, flexible, unfinished and in a permanent transformation.